Approach for GPS precise time transfer using an augmentation information and zero‐differenced PPP model. Issue 8 (1st August 2018) - Tu, Rui; Zhang, Pengfei; Zhang, Rui; Liu, Jinhai; Lu, Xiaochun
Abstract : This study proposes an approach for global positioning system (GPS) precise time transfer using the augmentation information and zero‐differenced precise point positioning (PPP) models. The augmentation information can be real‐time generated by constraining the coordinates of the reference stations, it is the difference between the observed distance and the real distance from the satellite to the receiver after considering the modelling errors. As the augmentation information contains the ionosphere delay, troposphere delay, receiver clock, phase ambiguities, ephemeris residuals and the other un‐modelling errors, thus some common errors are eliminated and/or reduced after used the augmentation information, then the zero‐differenced PPP model can be used for data solution and precise time transfer service. Two pairs of datasets were used to validate the feasibility and effectiveness of the proposed approach. The results show that the accuracy and stability of time transfer are greatly improved by the new approach, especially for the zero baseline. Compared with the traditional PPP time transfer approach, which relies on the precise ephemeris, the new approach used the augmentation correction which contains the ephemeris residuals, thus it can be operated by both precise ephemeris and broadcast ephemeris, and is hence more effective for real‐time operation.